Effects of the mGluR5 antagonist MPEP on ethanol withdrawal induced anxiety-like syndrome in rats - Kumar, Jaya; Hapidin, Hermizi; Get Bee, Yvonne-Tee; Ismail, Zalina (2013)
Abstinence from chronic ethanol consumption leads to the manifestation of a variety of symptoms attributed to central nervous system hyperexcitability, such as increased irritability, anxiety, and restlessness. Recent studies have demonstrated the importance of metabotropic glutamate receptor 5 (mGluR5) in addictive behaviours. This study investigates the effects of the mGluR5 antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP) on ethanol withdrawal induced anxiety using two behavioural paradigms. Male Wistar rats were fed a Modified Liquid Diet (MLD) containing low fat cow milk, sucrose, and maltodextrin with a gradual introduction of 2.4%, 4.8% and 7.2% ethanol for 20 days. Six hours into ethanol withdrawal, the rats were intraperitoneally injected with normal saline and MPEP (2.5, 5.0, 10, 20, 30 mg/kg) and were assessed for ethanol withdrawal induced anxiety-like syndrome using an automated elevated plus maze and an open field. MPEP at 10 mg/kg significantly attenuated ethanol withdrawal induced anxiety without any compromising effects on locomotor activities. Despite reversing several indices of ethanol withdrawal induced anxiety in both the elevated plus maze and the open field, low doses of MPEP (2.5, 5 mg/kg) significantly compromised the locomotor activities of ethanol withdrawn rats. High doses of MPEP (20 and 30 mg/kg) significantly attenuated withdrawal anxiety when tested in the elevated plus maze but not in the open field. Administration of MPEP (2.5, 5, 10, 20, 30 mg/kg) has no significant compromising effect on the locomotor activities of ethanol naïve rats. Despite significantly reducing withdrawal anxiety in both behavioural paradigms at 10 mg/kg, the compromising effects of low and high doses of MPEP must be further explored along with the therapeutic efficiency of this drug for relieving withdrawal induced anxiety.